Analisis Pengaruh Depresiasi Rupiah Terhadap Dolar Amerika Serikat Pada Bidang Ekspor Dan Impor - Ahmad Ardian Ari Sandi; Dinda Bharotut Taqiyah; Mohammad Harun Rifai; Rizky Yus Setiawan; Rizqi Trisnaningtyas; Agus Eko Sujianto (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study aims to analyze the effect of the depreciation of the Rupiah exchange rate against the US Dollar in the context of export and import activities in Indonesia. The research method used is a desk study, which involves collecting and analyzing data from various literatures, journals, and other academic sources. The results show that Rupiah depreciation has a significant impact on export and import activities. Rupiah depreciation tends to increase the competitiveness of Indonesian export products in the international market due to relatively cheaper prices in foreign currency. Conversely, imports become more expensive, which may reduce the volume of imported goods and services. This study also identifies other factors that affect the impact of depreciation, such as demand elasticity, production cost structure, and government policies. The conclusion of this study is that Rupiah depreciation has complex impacts that need to be properly managed through appropriate economic policies to maximize the benefits for the Indonesian economy.